KOMPARASI PARKIR ON STREET TERHADAP KINERJA JALAN DENGAN MEDIAN DAN JALAN TANPA MEDIAN MENGGUNAKAN METODE SIMULASI (STUDI KASUS JALAN KH. AGUS SALIM DAN JALAN PANDANARAN) - Denny Kusumanegara; Eko Bagus Cahyono; Ismiyati Ismiyati; Kami Hari Basuki (Jurnal Karya Teknik Sipil, 2015)
On street parking is parking which take place along of street. This parking gives a negative impact for traffic flow, because it can reduce width of road. The purpose of this study was to compare the on-street parking on one lane in Jalan KH. Agus Salim with median and Jalan Pandanaran without median toward the performance of the road, as well as provide an alternative parking management. Analysis of the data used is simulation method of flow theory based on Greenshields, Greenberg, and Underwood models. The largest value of the correlation coefficient (R) among the three models is taken to determine the model used. Based on the results of the simulation can be compared to the smooth flow of traffic in the presence of on-street parking on the road with median and the road without median.The analysis showed that the model of Greenberg is a model that best fits the characteristics of KH. Agus Salim and Pandanaran Street. The results of simulation analysis parking angle configuration at Jalan KH. Agus Salim on Thursday showed the DS of 0,231, 0,472, 0,223 respectively for the parking configuration 0°, 90°, without parking, while Saturday at 0,303, 0,619, 0,292 for the same parking configuration. These results indicate that the parking angle 0°, 90°, and no parking on the street with median provide good performance when viewed from the value of the DS which took on Thursday and Saturday. Value of DS at Pandanaran street as a result of on-street parking on Thursday and Saturday respectively 0,879, 1,981, 0,841 and 0,903, 2,035, 0,864 for the configuration of the parking angle 0°, 90°, and without parking. The simulation results indicate that without parking on Pandanaran street is the best solution, so that the comfort and safety in road traffic can be achieved. Alternative parking management given that, KH. Agus Salim use the parking angle of 0° to keep the facility u-turn, or use the parking angle of 30° but the u-turn facility closes. Jalan Pandanaran using angle of 0° and rotate prohibition direction, or providing off street parking in the surrounding area of Pandanaran and provide facilities vehicle turning direction. This research just analyze road performance on one lane, so that further research can be do for analyze on-street parking on two lanes in each of the road.